PENEGAKAN HUKUM KEHUTANAN DALAM UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN DITINJAU DARI PERSPEKTIF KEADILAN MASYARAKAT HUKUM ADAT - Rugun Romaida Hutabarat; Luisa Srihandayani; Kexia Goutama; Yoefanca Halim (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2019)
Forest destructions has been escalating worldwide, including in Indonesia. Therefore, the Government issued Law Number 18 / 2013 on the Prevention and Eradiction of Deforestation (P3H) which was expected to guarantee legal certainty with emphasis on eradication of organized forest destruction. The problem to be discussed in this paper is about law enforcement and application of Law Number 18 / 2013 which frequently used to criminalize the indigenous people in Indonesia. The indigenous people have been criminalized on the ground of unlawful forest products utilization, while they merely foraging to fulfill their basic necessities. The criminalization of indigenous people is a conclusive evidence, which proof that Indonesian Goverment has been neglecting the indigenous people’s right. This paper use normative approach. The conclusion of this paper analyze that the problem of the criminalization happens in implementation level, which caused by the ignorance of law enforcement apparatus and vested interest.